Fault Diagnosis of Rolling Bearings based on VMD and Symmetric Difference Energy Operator Demodulation - Qin Bo; Wang Zuda; Guo Huili; Sun Guodong; Chen Shuai; Wang Jianguo (Jixie chuandong)
Aiming at the problem of rolling bearing early fault vibration signals non-stationary and high noise,failure frequency is difficult to extract. A fault diagnosis method of rolling bearings based on the Variational Mode Decomposition（ VMD） and symmetric difference energy operator is proposed. First of all,the rolling bearing vibration signals are decomposed by VMD algorithm,a number of modal components are got. Secondly,according to the maximum kurtosis criterion,the modal component demodulated by symmetric difference energy operator is selected. Finally,a demodulated signal amplitude and frequency information are obtained and the envelope spectrum is calculated. The experimental results show that compared with the traditional energy operator,the proposed method can effectively extract the fault feature,and can restrain the false interference frequency and highlight the fault characteristic frequency,more conducive to roller bearing fault diagnosis.